PEMANTAUAN REAKSI OBAT MERUGIKAN DARI PENGGUNAAN OBAT ANTIINFLAMASI TERHADAP GASTROINTESTINAL - Yani Mulyani (JURNAL FARMASI GALENIKA, 2014)
Anti-inflammatory drugs are often prescribed in hospitals, especially in adult patients to treat pain, especially in joint disease. Anti-inflammatory drug that is used long term can cause gastrointestinal disturbances. This study aims to monitor adverse drug reactions from the use of anti-inflammatory drugs on the gastrointestinal. This study is a descriptive study using concurrent data is taken from the order signals in the inpatient unit involving 52 patients. This study includes several stages of the preliminary survey, the determination of medicine criteria, criteria of drug use, setting criteria of patients, collecting data from the order signal, there is a data source, data analysis and conclusions. The results showed that of the 52 patients there are 17.31% of patients get anti-inflammatory drug therapy (consisting of 11.53% receiving nonsteroidal anti-inflammatory drugs and 5.77% received antiinflammatory steroid) and received a gastrointestinal drug without gastrointestinal indications. Gastrointestinal drugs used were antiemetic 23.61%, 19.44% antacids, antiflatulen, 16.67, kolagogum 8.33%, 12.50% other gastrointestinal drugs, antidiarrheal 11.11%, 2.78% laxative, and digestan koreletikum 2.78%. Based on the results of this study concluded that the use of anti-inflammatory drugs either steroids or nonsteroidal can lead to gastrointestinal adverse drug reaction it gained 17.31%